Pemikiran dan Corak Tasawuf Hamka dalam Tafsir Al-Azhar - Masrur Masrur (Medina-te : Jurnal Studi Islam, 2016)
The written examined efforts to analyze the thought and Sufism patterns of HAMKA. HAMKA was one figure of Indonesian Muslim intellectual who had given significant contributions in the Islamic sciences. Among the many creations of Hamka was Tafsir al-Azhar and several books related to mysticism, one of them was a modern Sufism. in his monumental  creation  Tafsir al-Azhar, HAMKA peeled many verses of Qur'an relating to the specifics of  Sufism, including: Tauba, zuhd, resignation, Rida, wara ', qana'a, and mahabbah. Hamka more patterned his interpretation of Sufism akhlāqy. The characteristic of Sufism pattern such as emphasizing perfection and sanctity of life were formulated on the setting of mental attitude and discipline behavior, it clearly was the substance of Sufism offered HAMKA in this life. For the attainment of optimal happiness human existence should identify themselves with the characteristics of divinity in tazkiyat al-nafs as a first step that must be done, in Sufism sciences   riyādhah steps were known as takhalli, tahalli and tajalli.